Pengembangan E-Modul Pelatihan Berbasis Self-Directed Learning Tentang Pembuatan Materi Pembelajaran Metode Flipped Classroom - Palupi, Ester Sekar; Mawardi, Mawardi; Iriani, Ade (Kelola: Jurnal Manajemen Pendidikan, 2023)
This study aimed to develop and evaluate a Self-Directed Learning (SDL)-based e-module on Flipped Classroom learning material creation for English teachers in junior high schools in Salatiga and describes the weaknesses of the English learning material development training that has been implemented in junior high schools in Salatiga. The subjects of this research are English teachers in junior high schools. The type of research is Research and Development (R&D) by using model Sugiyono with mixed method sequential exploratory research approach. Data collection techniques used interviews, documentation studies, and questionnaires. Data validation techniques were carried out by triangulating sources and techniques. The development stage is carried out through: (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation and (5) Design Improvement. (6) Limited Trial to 40 Teachers of 2 training classes, namely: experimental class 20 people and control class 20 people. Qualitative data analysis techniques use qualitative data analysis models based on Milles & Huberman (1994), namely data reduction, data display, and conclusions drawing and verification. Quantitative data analysis in the form of pretest and post test scores will be analyzed using SPSS Paired T test analysis. The results of this study show that the weaknesses of the training carried out so far have only focused on administrative training for teachers, as well as inflexible implementation time. Based on the field trial, there was an increase in the results of the pre-test and post-test for participants. However, the researcher could not find out how far the influence of this self-directed learning module on the motivation of participants in learning the material provided. .